THE EFFECT OF TRUST AND PARTICIPATORY ATTITUDES ON VILLAGE FINANCIAL REPORTING TRANSPARENCY WITH THE PERCEPTION OF BUDGETARY FAIRNESS AS A MODERATING VARIABLE (A STUDY OF VILLAGES IN BALAESANG DISTRICT, DONGGALA REGENCY): - Meilita, Findi; Usman, Rudy; Yamin, Nina Yusnita; Betty, Betty (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
Abstract This study aims to analyze the influence of public trust and participatory attitudes on the transparency of village financial reporting, with perceptions of budget fairness as a moderating variable. The study used a quantitative approach with a survey method in village communities in Balaesang District, Donggala Regency. The sample was determined using the Slovin formula with 100 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares with the help of WarpPLS. The results showed that public trust and participatory attitudes had a positive effect on the transparency of village financial reporting. Participatory attitudes had a more dominant influence than public trust. Perceptions of budget fairness did not act as a moderating variable in this relationship. Transparency of village financial reporting was more influenced by direct factors such as public trust and involvement than by assessments of budget fairness. The implications of this study indicate the importance of increasing public trust and participation in encouraging the transparency of village financial information. Village governments need to strengthen public communication and actively involve the community in the financial management process. Keywords: Public Trust, Participation, Transparency, Budget Fairness, Village Financial Reporting.